The case of TUI : sailing into a bright future or sinking like Thomas Cook? - Schäfer, Jana Christina (2020)
In the rapidly changing environment of the tourism industry, it becomes crucial for its players to adapt to exogenous factors in order to stay competitive and profitable in the long run. As an increasing number of tourists were individually booking their holidays through online booking portals, the business model of pure tour operators was being undermined. While some players, like TUI, saw the digitalization as an opportunity to change its business model, others, like Thomas Cook, failed to adapt. The case of TUI, one of the largest tourism groups worldwide, serves as an example of a successful strategic change and fit to environmental and organizational contingencies. The case demonstrates how TUI transformed its business model from a traditional tour operator towards a fully vertically integrated provider of holiday experiences. The new management introduced a strategic initiative in 2013, which involved the important merger of the parent company TUI AG with its subsidiary TUI Travel to reach full vertical integration. Thereafter, TUI highly invested in assets in terms of hotels and cruise ships as well as destination experiences. It illustrates, that the management made use of Dynamic Capabilities and changed the company’s resource base through the corporate strategy of vertical integration, in particular in the form of taper integration. Although the strategic change had proven to be successful, the vertical integration exposed the group to enormous financial challenges, when the corona pandemic brought the world to a standstill in 2020.